Cowpea genetic variability analyzed by RAPD markers - Xavier, Gustavo Ribeiro; Martins, Lindete Miria Vieira; Rumjanek, Norma Gouvêa; Filho, Francisco Rodrigues Freire (Pesquisa Agropecuaria Brasileira, 2005)
The knowledge on genetic variability and the relationship among different cowpea accesses is important to maximize resource use represented by available cowpea genotypes. The objective of this work was to determine the genetic variability among 45 cowpea (Vigna unguiculata (L.) Walp.) accesses from Brazil, USA and Niger, characterized by RAPD (Random Amplified Polymorphic DNA) markers. Eight polymorphic primers were identified, comprehending a total of 48 informative bands. Based on the obtained polymorphic profiles, four major clusters were formed. Clustering was mainly influenced by the genotype origin. Most accesses from Brazilian landraces belong to just one cluster, suggesting a limited genetic basis. It is worth noting that none of the genotypes from Niger considered as possessing superior agronomical traits, such as high productivity, was present in this cluster. RAPD shows to be an efficient tool, capable of assisting cowpea genotype selection adapted to Brazilian edaphoclimatic conditions, aiming at increasing productivity and improving other desirable characteristics to meet the needs of specific regional demands.